TEKNOLOGI TRUE SHALLOTS SEED DAN PEMANFAATAN LIMBAH PERTANIAN PADA PERTUMBUHAN PRODUKSI BAWANG MERAH (Allium Ascalonicum L) - Tharmizi Hakim; Devi Andriani Luta, Diki Syahputra Sitepu (PROSIDING, 2022)
Shallots (Allium ascalonicum L) are included in the superior national product. In increasing the production of shallots, fertilizers containing complete nutrients are needed from various agricultural wastes which are fermented anaerobically to obtain solid and liquid organic fertilizers. This research method uses a factorial Randomized Block Design (RAK) consisting of 2 factors studied with 16 treatment combinations and 2 replications. Factor I solid organic fertilizer (P) with a level of 0 kg/plot, 1.5 kg/plot, 2.5 kg/plot, 3.5 kg/plot, and factor 2 liquid organic fertilizer (C) with a level of 0 ml/liter water/plot, 250 ml/liter of water/plot, 450 ml/liter of water/plot, 650 ml/liter of water/plot. Parameters observed were plant height (cm), wet tuber weight (g), dry tuber weight (g), and production conversion per hectare (kg). The results of the study of the 4 parameters gave a significant effect on the 2 treatments. This is what the researcher hopes for and it is recommended that further research be carried out by providing a higher level of treatment for this research. Keywords: fertilizer. solid, liquid, shallot, red.